(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-178-187 The purpose of the article is to show the irreconcilable position of liberal publicists in relation to the tsarist regime on the eve of the first Russian revolution of 1905-1907 and during the period of active association of liberals around the foreign opposition magazine Osvobozhdenie (1902-1905). Unlike the social-democratic newspaper Iskra and the Socialist-Revolutionary Russia, which developed their party programs for a certain class – workers and peasants, respectively – Osvobozhdenie set the task of a nationwide movement in the struggle for their rights. Therefore, in addition to leading articles, analytical reviews, program speeches by the leaders of the future movement, political satire was actively used in the Osvobozhdenie magazine as a method of political struggle against the tsarist autocracy and effective propaganda against the existing regime. Key words: Osvobozhdenie magazine, liberalism, autocracy, political satire, pamphle